Studi Living Tafsir terhadap Tradisi Sekar Sari Kidung Rahayu pada Paguyuban Macapat Tresna Budaya - Wildan Fahdika Ahmad (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
The interpretation of the Qur'an today is no longer just a text of interpretation of the Qur'an collected between two covers. Several studies have shown that the interpretation of the Qur'an lives in society, known as